GEOMORPHOLOGICAL AND PALEOENVIRONMENTAL CHANGES OF ISMARIDA LAKE DURING HOLOCENE (N. GREECE) - Karadimou, G.; Vouvalidis, K.; Syrides, G.; Koukousioura, O.; Aidona, E. (Bulletin of the Geological Society of Greece, 2016)
In this research, the geomorphological and environmental changes of Lake Ismarida during Holocene are studied. Ismarida is located 20Km south of Komotini city and 5Km NNE of the archeological site of ancient Stryme at Rhodope Province, (N. Greece). The analysis of geomorphological, paleontological, sedimentological and magnetic susceptibility data as well as the evaluation of 14C datings, showed that four environmental units are recognized in the lake sediments. The environment changed from shallow marine to open lagoonal of low energy ( 5400-3400 years BP), to shallow marine to open lagoonal of high energy ( 3400-3000 years BP), subsequently turned into brackish to lagoonal with fresh water inputs ( 3000-2000 years BP), and finally formed to fluvial-terrestrial, until present time. The Lake Ismarida as it is known today was formed 2000 years BP on the isolated western part of th pre-Holocene valley between the deltaic deposits of the rivers Filiouris and Vosvozis.